Speech text of memorandum of understanding (MoU) exchange between Universiti Teknologi MARA (UiTM) and Jerash University (JU), Zarqa University (ZU), Ajloan University (AU), and Amman Arab University (AAU) / Prof. Datuk Dr. Shahrin Sahib @ Sahibuddin - Sahib @ Sahibuddin, Shahrin (2024)
1) Alhamdulillah, praise be to Allah S.W.T for His abundant blessings, which made it possible for us to gather today to witness the beginning of a meaningful collaboration. 2) I extend a cordial welcome and Selamat Datang to all eminent guests. I am delighted to have the honour of joining you today for the Memorandum of Understanding (MoU) exchange between Universiti Teknologi MARA (UiTM) and four (4) Jordanian universities, namely the Jerash University, Zarqa University, Ajloan University, and the Amman Arab University.